2017
DOI: 10.1186/s13052-017-0409-1
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for preventing group B streptococcal infections in newborns: a nation-wide survey of Italian policies

Abstract: BackgroundThere are no Italian data regarding the strategies for preventing neonatal group B streptococcal (GBS) infection. We conducted a national survey in order to explore obstetrical, neonatal and microbiological practices for the GBS prevention.MethodsThree distinct questionnaires were sent to obstetricians, neonatologists and microbiologists. Questionnaires included data on prenatal GBS screening, maternal risk factors, intrapartum antibiotic prophylaxis, microbiological information concerning specimen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…As preterm neonates younger than 34 weeks’ gestation need special care in NICUs, we focused on late preterm (34–36 weeks’ gestation) and full-term (≥37 weeks’ gestation) neonates, that account for over 90% of total deliveries and are managed in all birthing centers across country. The recent national survey [ 4 ] has shown that great resources are poored into prevention of EOS, and often are given unnecessary antibiotics. Ancillary laboratory tests currently available are low predictive for asymptomatic neonates and have insufficient accuracy for guiding the decision as to whether neonates should be treated with antibiotics [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As preterm neonates younger than 34 weeks’ gestation need special care in NICUs, we focused on late preterm (34–36 weeks’ gestation) and full-term (≥37 weeks’ gestation) neonates, that account for over 90% of total deliveries and are managed in all birthing centers across country. The recent national survey [ 4 ] has shown that great resources are poored into prevention of EOS, and often are given unnecessary antibiotics. Ancillary laboratory tests currently available are low predictive for asymptomatic neonates and have insufficient accuracy for guiding the decision as to whether neonates should be treated with antibiotics [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent national survey [ 4 ] shows that the screening-based strategy is largely prevalent and protocols in most centers are consistent with the CDC guidelines [ 1 ]. However, differences in GBS EOS sepsis occur among Northern, Central and Southern regions.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…The EOGBS incidence at our hospitals was 0.38 per 1000 live births in the era of universal GBS screening, but this decline was not as dramatic as that observed in Western countries. 16,17 More than 60% of the EOGBS neonates were born to women with negative screening results. 1,18,19 Reasons for this missed opportunity for GBS prevention include serotype-specific colonization patterns and inadequate rectovaginal sampling.…”
Section: + Modelmentioning
confidence: 99%
“…2,3 Moreover, there is a risk that the child may be colonized during delivery, which occasionally causes "early onset disease" (EOD), which is associated with PPROM. [3][4][5][6] Intrauterine infection is assumed to arise from vaginal bacteria that pass through the cervical canal, gain access to the decidua, and invade and cross the intact chorioamniotic membranes to access the amniotic cavity. 7 However, infections do not always elicit inflammatory responses or PPROM.…”
Section: Introductionmentioning
confidence: 99%